The Prominent Role of Tarekat Education as A Social Change Basis for Stemming Radicalism in Lamongan - Rohman, Abdul; Rouf, Abdullah Zainur; Kusbandhono, Erryk; Hazyimara, Karunia; Defriono , Ilham (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This article examines the role of Tarekat (Sufi) educational institutions in promoting social change in Lamongan, Indonesia, a region known for Islamic radicalism. Tarekat institutions have often been seen as disconnected from social change, primarily seen as ascetic and otherworldly, not concerned with social issues. However, this study argues that these institutions can play a crucial role in countering radicalism. While government efforts to counter radicalism and deradicalisation focus on conventional methods, tarekat institutions remain undervalued as cultural assets in this context. The research uses a qualitative phenomenological approach, including interviews, observation and documentation. Findings suggest that Sufi educational institutions are instrumental in curbing the spread of radicalism, particularly in Solokuro, Lamongan. The curriculum, which emphasises peace and love, contributes significantly to deradicalisation efforts and provides an effective cultural countermeasure to radicalism in the region.